The Existence Of Women In Social Structure Minangkabau Community In Ka'bati's Padusi Novel - Fitri, Annisa (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
This research is motivated by the story of a Minangkabau female character in Ka'bati's Padusi Novel who has left the traditional social structure, that is, did not receive an inheritance and received abuse and violence from her husband so she went abroad to earn a living to save her family's life. Therefore, this study aims to reveal and explain the existence of: (1) the true role and function of women in Minangkabau customs and culture; (2) the roles and functions of Minangkabau women as described in Ka'bati's Padusi novel; and (3) the causes of the shift in the existence of women's roles and functions in the Minangkabau social structure in the Padusi Novel. This type of research is qualitative using descriptive method. The data of this research are words, sentences, and discourses that show the roles and functions of Minangkabau women which originate from the novel Padusi by Ka'bati. Based on this research, the existence of Minangkabau women was found as follows. First, the role and function of women according to the provisions of Minangkabau customs and culture are as holders and managers of inheritance (inheritance) and at the same time have a special and noble position in the hereditary system of their people. Second, however, in the novel the conditions and circumstances experienced by the female characters are not in accordance with the provisions of these customs, namely the loss of women's rights to inheritance and ulayat land so that women have to migrate to earn a living and also experience physical and mental violence from husband. Third, the changing roles and functions of women in the novel are caused by several factors, namely changes in the social environment, economic factors, and the occurrence of modernity. Thus, because literature is a reflection of the condition of society, it can be concluded that there has been a change in the role of Minangkabau women, namely taking over the function of men to meet the needs and survival of their families. Conversely, the role of men is weakened due to lack of responsibility and low fighting power and effort.